Description of lithologic section units of IODP Hole 386-M0088A - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Description of lithologic section units from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The content of this dataset is based on the visual core descriptions (VCD) done by sedimentologists during the onshore phase of expedition 386 (2022-02-14 – 2022-03-15 onboard D/V Chikyu). For digitalization of the information, content of the hand-drawn VCD sheets was transferred into the Drilling Information System database. The present dataset forms the basis for the digital lithologic columns and composite plots archived under the titles "Visual core description of IODP Hole 386-M0088A". For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023